PENGARUH INOVASI PRODUK TERHADAP KINERJA USAHA DENGAN KEUNGGULAN BERSAING SEBAGAI VARIABEL MEDIASI PADA USAHA MINUMAN BOBA DI KOTA PEKANBARU - Hardiana Nafrianti; Samsir Samsir; Anggia Paramitha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of product innovation on businessperformance with competitive advantage as mediation variable at boba drinkenterprise in Pekanbaru City. The population of study included all boba drinkenterprise in Pekanbaru City were 83 units and the samples were 69 units, it’sbased on Slovin formula. Structural Equation Model (SEM) with SmartPLSversion 3 was used as methods of data analysis. The results were: 1) Innovationproduct had positive and significant effect on competitive advantage; 2)Innovation product had positive and significant effect on business performance;3) Competitive advantage had positive and significant effect on businessperformance; 4) Innovation product had positive and significant effect onbusiness performance throughwork competitive advantage. Keyword: Innovation Product, Competitive Advantage, Business Performance.